1983
DOI: 10.1093/ajcp/79.3.348
|View full text |Cite
|
Sign up to set email alerts
|

A High Prevalence of Hypomagnesemia and Hypermagnesemia in Hospitalized Patients

Abstract: The prevalence of hypomagnesemia and hypermagnesemia among hospitalized patients was studied by determining magnesium levels in 621 serum samples randomly selected from those submitted to the clinical chemistry laboratory for a biochemical test panel. The reference range for serum magnesium was established in this study as 1.2 to 1.9 mEq/L from measurements of serum magnesium on 341 healthy volunteers. Hypomagnesemia (less than 1.2 mEq/L) was present in 68 patients or 11.0%, and hypermagnesemia (greater than 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1
9

Year Published

1984
1984
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(60 citation statements)
references
References 0 publications
2
48
1
9
Order By: Relevance
“…For example, we had to exclude two studies(11, 23) from the meta-analysis because they reported mean CRP (SD), and/or OR (95%CI) based on a continuous scale of Mg intake. Second, none of the primary studies considered the health impact of high Mg intake (hypermagnesaemia, e.g., serum Mg>1.9 mEq/L(28)). Anyway, no sufficient evidence to date indicates any substantial adverse effect of dietary magnesium overdose, though two case studies reported that Mg intake above 6 mEq/L, a rare phenomenon in a general population, caused parathyroid gland dysfunction, respiratory, cardiac and CNS dysfunction(29, 30).…”
Section: Discussionmentioning
confidence: 99%
“…For example, we had to exclude two studies(11, 23) from the meta-analysis because they reported mean CRP (SD), and/or OR (95%CI) based on a continuous scale of Mg intake. Second, none of the primary studies considered the health impact of high Mg intake (hypermagnesaemia, e.g., serum Mg>1.9 mEq/L(28)). Anyway, no sufficient evidence to date indicates any substantial adverse effect of dietary magnesium overdose, though two case studies reported that Mg intake above 6 mEq/L, a rare phenomenon in a general population, caused parathyroid gland dysfunction, respiratory, cardiac and CNS dysfunction(29, 30).…”
Section: Discussionmentioning
confidence: 99%
“…A prevalence of 11% was reported when 621 hospital patients (in the USA) were randomly selected compared to 2.5% in the control group made up of 341 hospital staff [31]. Other disease conditions such as malabsorption, diarrhea, hypertension, cognitive heart failure, coronary artery disease among others have all been reported to be associated with hypomagnesaemia [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic hypermagnesemia is rare and mostly induced by excessive use of drugs which contain high amounts of Mg 2+ , including laxatives and Epsom salts [1]. Hypomagnesemia on the other hand is more frequent [810] and can have several distinct causes. First among these is a prolonged general loss of electrolytes, such as during periods of vomiting, diarrhea or malabsorption [11].…”
Section: Disturbances Of Mg2+ Homeostasismentioning
confidence: 99%